Synthesis and evaluation of a radioiodinated 4, 6-diaryl-3-cyano-2-pyridinone derivative as a survivin targeting SPECT probe for tumor imaging. Issue 3 (1st February 2016) - Fuchigami, Takeshi; Mizoguchi, Tatsuya; Ishikawa, Natsumi; Haratake, Mamoru; Yoshida, Sakura; Magata, Yasuhiro; Nakayama, Morio
Graphical abstract: We report here a radioiodinated 4, 6-diaryl-3-cyano-2-pyridinone derivative (IDCP) as a survivin targeting SPECT probe for tumor imaging. Abstract: Survivin is overexpressed in most of the cancerous tissues but not in terminally differentiated normal tissues, making it an attractive target for diagnosis and therapy of various types of cancers. In this study, we aimed to develop 4, 6-diaryl-3-cyano-2-pyridinone (DCP) derivatives, as novel cancer imaging probes that target survivin. Chloro and iodo analogs of DCP (CDCP and IDCP, respectively) were successfully synthesized by using a previously unreported carbon monoxide-free procedure. IDCP exhibited a slightly higher binding affinity for recombinant human survivin ( K d  = 34 nM) than that of CDCP ( K d  = 44 nM). Fluorescence staining indicated that both CDCP and IDCP showed high signals in MDA-MB-231 cells with high levels of survivin expression. Significantly low fluorescent signals were observed in MCF-10A cells, which showed low levels of survivin expression. [ 125 I]IDCP was synthesized for the application of IDCP to single photon emission computed tomography (SPECT) imaging. Quantitative in vitro binding of [ 125 I]IDCP in cell cultures showed results consistent to those observed after fluorescent staining. In vivo biodistribution studies in tumor-bearing mice demonstrated that the tumor uptake of [ 125 I]IDCP increased gradually with time and was 0.65% injected dose per gram (% ID/g) at 180 min. The maximum tumor/blood and tumor/muscle ratio at 60 min were 0.87 and 2.27, respectively, indicating inadequate [ 125 I]IDCP accumulation in tumors necessary for in vivo imaging. Although further structural modifications are necessary to improve pharmacokinetic properties of IDCP, this study demonstrates the feasibility of using the DCP backbone as a scaffold for the development of survivin-targeting tumor imaging probes.